Ageing of thermosets based on tung oil/styrene/divinylbenzene - Meiorin, Cintia (2012)
New thermoset polymers prepared by cationic co-polymerization of tung oil with styrene and/or divinylbenzene were evaluated at different times after their preparation. The changes in the properties were correlated with the composition of the copolymers. The action of atmospheric oxygen on the fatty acid unsaturations produced chemical changes in these polymers, which affected the properties of the cured materials. These changes were analyzed by FTIR, dynamic mechanical properties and mechanical testing. An increase in the modulus with time for all the analyzed samples was observed, as well as a large effect on the glass transition temperature and, consequently, in the shape memory properties.